Re-Engineering on the Production of Surrogate Feeds for Broiler Chickens (Gallus–Gallus Domesticus): its Effects on Broilers’ Live and Carcass Weights and Consumption Cost - Subia, Gener S.; Mina, Jennilyn C.; Diaz, Rowell A.; Campos, Romeo B.; Jr., Jr.; Quijano, Gerald (International Journal of Environment, Agriculture and Biotechnology, 2019)
This experimental study focused on the production of alternative feeds for broilers chickens using golden apple snail shell as the main ingredient. Three groups were compared and the characteristics of them are as follows: The commercial group was given pure commercial feeds, treatment one group (T1) was given 25% pomaceacanaliculata’s shell that was mixed with 37.5% of rice bran and 37.5% of corn, and the third group which was treatment (T2) was given 50% pomaceacanaliculata’s shell that was mixed with 25% of rice bran and 25% of corn as feed mix.The study found out that golden apple snail shell can be mixed with feeds for broiler production without negative effect on the carcass recovery. It can replace commercial feeds as food for broilers especially if the farm area or area near it were infested by golden apple snail. Although the consumption cost among the treatments and the commercial feed do not differ, it is practical to use T2 as a substitute for commercial feeds since it is less than P3.00 to P5.00 per consumption cost. The findings of this study have valuable financial implications, particularly to the farmers and poultry owners